The point of view of professionals of health on HIV/AIDS advising: a Paulo Freire proposal - Karla Corrêa Lima Miranda; Maria Grasiela Teixeira Barroso (Rev Rene)
This descriptive study aims at identifying the advising concept by professionals of health in an HIV/AIDS service. Nine professionals of health, like nurses, social workers and psychologists, who work in the advising service, were interviewed. Direct observation, interview script and field diary were used. The study showed that the way people advise on HIV/AIDS is personal and many times, depending on how the professional sees this activity, it brings his profile in it. The group studied was able to formulate a concept, but it still is too close to the one defended by the Ministry of Health, not beeing visualized as an educative moment in a wider way. We suggested the group to think about the advising activity and proposed advising based on Paulo Freire’s concepts.